Chinese botanical drugs targeting mitophagy to alleviate diabetic kidney disease, a comprehensive review - Ma, Leilei; Li, Jing; Zhang, Xiaotian; Zhang, Wei; Jiang, Chen; Yang, Bo; Yang, Hongtao (Frontiers in Pharmacology, 2024)
Diabetic kidney disease (DKD) is one of the chronic microvascular complications caused by diabetes, which is characterized by persistent albuminuria and/or progressive decline of estimated glomerular filtration rate (eGFR), and has been the major cause of dialysis around the world. At present, although the treatments for DKD including lifestyle modification, glycemic control and even using of Sodium-glucose cotransporter 2 (SGLT2) inhibitors can relieve kidney damage caused to a certain extent, there is still a lack of effective treatment schemes that can prevent DKD progressing to ESRD. It is urgent to find new complementary and effective therapeutic agents. Growing animal researches show that mitophagy makes a great difference to the pathogenesis of DKD, therefore, exploration of new drugs that target the restoration of mitophagy mabe a potential perspective of treatment for DKD. The use of Chinese botanical drugs (CBD) has been identified to be an effective treatment option for DKD.There is growing concern on the molecular mechanism of CBD for treatment of DKD by regulating mitophagy. In this review, we highlight the current findings regarding the function of mitophagy in the pathological damages and progression of DKD and summarize the contributions of CBD that ameliorate renal injuries in DKD by interfering with mitophagy, which will help us further explain the mechanism of CBD in treatment for DKD and explore potential therapeutic strategies for DKD.